Lived experiences, coping strategies, and resilience of internally displaced mothers of the Marawi siege. - Acallar, Ma. Lory Jen D. (2018.)
The study was conducted to describe the experiences of mothers while evacuing as the Marawi Siege occurred, their circumstances at the evacuation center, and the challenges that they experienced when the siege ended to determine their different coping strategies and to determine their level of resilience. Fifteen (15) Internally displaced mothers served as respondents to the study. All were residents of Marawi, were present at the time the city was attacked, and were evacuated until they have settled in an evacuation center. Three instruments were utilized namely: an interview guide, Ways of Coping (Revised) by Folkman (1985), and the Resilience Research Center ? Adult Resilience Measure (RRC ? ARM) (2016). Results of the study revealed several themes. Majority of the respondents employed seeking social support as their coping strategy. All of the respondents had high levels of resilience.
Research Project (Undergraduate, Bachelor of Arts (Psychology) College of Arts and Sciences, University of the Philippines, Miagao, Iloilo. 2018.
Keywords: Mothers, Displaced -- Marawi Siege